Deprescribing: An umbrella review - Japelj Nuša; Horvat Nejc; Knez Lea; Kos Mitja (Acta Pharmaceutica)
This umbrella review examined systematic reviews of deprescribing studies by characteristics of intervention, population, medicine, and setting. Clinical and humanistic outcomes, barriers and facilitators, and tools for deprescribing are presented. The Medline database was used. The search was limited to systematic reviews and meta-analyses published in English up to April 2022. Reviews reporting deprescribing were included, while those where depre-scribing was not planned and supervised by a healthcare professional were excluded. A total of 94 systematic reviews (23 meta--analyses) were included. Most explored clinical or humanistic outcomes (70/94, 74 %); less explored attitudes, facilitators, or barriers to deprescribing (17/94, 18 %); few focused on tools (8/94, 8.5 %). Reviews assessing clinical or humanistic outcomes were divided into two groups: reviews with deprescribing intervention trials (39/70, 56 %; 16 reviewing specific deprescribing interventions and 23 broad medication optimisation interventions), and reviews with medication cessation trials (31/70, 44 %). Deprescribing was feasible and resulted in a reduction of inappropriate medications in reviews with deprescribing intervention trials. Complex broad medication optimisation interventions were shown to reduce hospitalisation, falls, and mortality rates. In reviews of medication cessation trials, a higher frequency of adverse drug withdrawal events underscores the importance of prioritizing patient safety and exercising caution when stopping medicines, particularly in patients with clear and appropriate indications.